Analisis Hubungan Kecerdasan Intelektual Dan Spiritual Dengan Hasil Belajar Aqidah Ahlak Peserta Didik di Maderasah - Aini Nur Ma'rifah (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2019)
This study aims to describe and explain Relationship of intellectual intelligence with learning outcomes Aqidah Ahlak learners MA Al-Mubarok, Relationship of spiritual intelligence with learning outcomes Aqidah ahlak students MA Al-Mubarok, the relationship of intellectual and spiritual intelligence together with learning outcomes Aqidah Ahlak students MA Al-Mubarok. This study uses a quantitative approach.Population of 220 students and 44 samples with random sampling technique. The research data collected using questionnaires and documents. Tehknis data analysis of this study using multiple linear regression. The results of this study are (1) There is a relationship of intellectual intelligence with learning outcomes Aqidah Akhlak learners MA Al-Mubarok this is based on result (thitung > ttabel yaitu 2.573> 2.020 with significan to 0,014 di mana < 0,050,014 where < 0,05. (2) There is a relationship of spiritual intelligence with learning outcomes Aqidah Akhlak Students MA Al-Mubarok this is based on result thitung ˃ ttabel yaitu 2.571 lebih besar dari ttabel 2.020 dengan signifikan sebesar 0,014 di mana < 0,05.(3) There is a relationship between intellectual and spiritual intelligence with the results of learning Aqidah Akhlak together with the learning outcomes Aqidah Ahlak students MA Al-Mubarok this is based on result signifikansi Fhitung˃Ftabel yaitu 11.847 lebih besar dari F tabel 0,323 dengan Sig Uji F: 0,000< 0,05 this shows acceptance to hypothesis there is positive relation which significant of intellectual intelligence and spiritual intelligence together with result of learning of Al-Mubarok’s student moral behavior